METHODOLOGY OF RESEARCH OF THE PROBLEM OF DIPLOMATIC STAFF TRAINING IN THE VISEGRAD GROUP COUNTRIES (1991-2004) - Савчук, Андрей (SWorldJournal, 2020)
The article analyzes some aspects of the methodology of researching the problem of diplomatic staff training in the Visegrad Group countries (1991-2004). It is argued that a comprehensive study of the diplomatic education system in the Visegrad countries,